Are judicial monitoring institutions a legitimate remedy for addressing systemic socioeconomic rights violations?. Issue 4 (1st October 2020) - Maphosa, Ropafadzo
Abstract: Sections 26(2) and 27(2) of the Constitution of the Republic of South Africa, 1996 provide that the state must take reasonable legislative and other measures to ensure the progressive realisation of socio-economic rights including, housing and social security. The executive is generally responsible for the implementation of these rights. However, a core challenge in South Africa is that the executive is beset by chronic incapacity, especially at provincial and local government levels, which has hindered the realisation of socio-economic rights. This article investigates the increasingly intrusive orders by the judiciary to address this problem; these orders include, specifically, appointing bodies to manage service delivery by the executive. I will situate these mechanisms within the broader powers of the judiciary and provide a justification for them, under particular conditions, against criticisms of judicial overreach. In engaging with their legal justifiability, I will analyse recent South African case law as well as examples from India and Colombia so as to highlight that the South Africa judiciary is not unique in developing such mechanisms. In concluding, I identify the conditions under which the deployment of these mechanisms may be considered justifiable as well as their value in advancing the realisation of socio-economic rights in South Africa.